Reading Ability and Behavior in Adolescents with Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Thirty-four adolescents with epilepsy, controls matched for age, sex, and general ability, were studied at the University Hospital, Cardiff, Wales.